2020
DOI: 10.1002/cncr.33095
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical benefit and cost of breakthrough cancer drugs approved by the US Food and Drug Administration

Abstract: Background The clinical benefit and pricing of breakthrough‐designated cancer drugs are uncertain. This study compares the magnitude of the clinical benefit and monthly price of new and supplemental breakthrough‐designated and non–breakthrough‐designated cancer drug approvals. Methods A cross‐sectional cohort comprised approvals of cancer drugs for solid tumors from July 2012 to December 2017. For each indication, the clinical benefit from the pivotal trials was scored via validated frameworks: the American So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
2
22
0
Order By: Relevance
“…The study findings, which are consistent with a previous study of FDA designated breakthrough cancer drugs and an analysis stratifying new drug approvals by novelty of mechanism of action,242526 suggest a widening gap between regulatory approval and the clinical and public health priorities of health systems, payers, and patients after approval. Contributing to this may be the varying quality of clinical trial evidence available at the time of approval and resulting uncertainty around the extent of clinical benefit 272829.…”
Section: Discussionsupporting
confidence: 88%
“…The study findings, which are consistent with a previous study of FDA designated breakthrough cancer drugs and an analysis stratifying new drug approvals by novelty of mechanism of action,242526 suggest a widening gap between regulatory approval and the clinical and public health priorities of health systems, payers, and patients after approval. Contributing to this may be the varying quality of clinical trial evidence available at the time of approval and resulting uncertainty around the extent of clinical benefit 272829.…”
Section: Discussionsupporting
confidence: 88%
“…Having said this, Salas-Vega in their analysis found that 43% of new oncology medicines approved either by the FDA or the European Medicines Agency (EMA) between 2003 and 2013, and subsequently reviewed by health technology agencies, did improve overall survival by 3 months or longer [72]. In addition, as mentioned, Molto et al (2020) found that 40% of new treatments recently received a breakthrough therapy designation, and were more likely than non-breakthrough therapies to provide a high clinical benefit [10]. Consequently, minimum thresholds of three to six months are likely to remain.…”
Section: Minimum Effectiveness Criteriamentioning
confidence: 99%
“…However, there are concerns with reimbursed prices for new oncology medicines, especially among higher-income countries and the actual level of health gain seen [8,9]. However, Molto et al (2020) found that 40% of new oncology medicines recently received a breakthrough therapy designation, and were more likely than non-breakthrough therapies to provide a meaningful clinical benefit [10]. In addition, Lauenroth et al (2020) found that the reforms in Germany led to reimbursed prices for new oncology medicines falling following evaluation; subsequently, more in line with the clinical benefit seen [11].…”
Section: Introductionmentioning
confidence: 99%
“…Antineoplastic drugs account for a large and growing share of drugs in development and new drug approvals 1 . Most are approved on the basis of randomized trials, yet the value of new drugs in a real‐world setting remains unclear 2 . Drugs tested in phase 3 trials must demonstrate a clinical benefit over the control‐arm therapy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Most are approved on the basis of randomized trials, yet the value of new drugs in a real-world setting remains unclear. 2 Drugs tested in phase 3 trials must demonstrate a clinical benefit over the control-arm therapy. However, the comparator may not always reflect the most recent treatment available to patients at the time the drug is approved because of the long duration of oncology clinical trials, especially when multiple drugs come to market at the same time.…”
Section: Introductionmentioning
confidence: 99%